Electronic and Magnetic Characterization of Epitaxial CrBr3 Monolayers on a Superconducting Substrate. Issue 23 (3rd May 2021) - Kezilebieke, Shawulienu; Silveira, Orlando J.; Huda, Md N.; Vaňo, Viliam; Aapro, Markus; Ganguli, Somesh Chandra; Lahtinen, Jouko; Mansell, Rhodri; van Dijken, Sebastiaan; Foster, Adam S.; Liljeroth, Peter
Abstract: The ability to imprint a given material property to another through a proximity effect in layered 2D materials has opened the way to the creation of designer materials. Here, molecular‐beam epitaxy is used for direct synthesis of a superconductor–ferromagnet heterostructure by combining superconducting niobium diselenide (NbSe2 ) with the monolayer ferromagnetic chromium tribromide (CrBr3 ). Using different characterization techniques and density‐functional theory calculations, it is confirmed that the CrBr3 monolayer retains its ferromagnetic ordering with a magnetocrystalline anisotropy favoring an out‐of‐plane spin orientation. Low‐temperature scanning tunneling microscopy measurements show a slight reduction of the superconducting gap of NbSe2 and the formation of a vortex lattice on the CrBr3 layer in experiments under an external magnetic field. The results contribute to the broader framework of exploiting proximity effects to realize novel phenomena in 2D heterostructures. Abstract : The electronic and magnetic properties of a 2D monolayer ferromagnet on a layered superconducting substrate are studied using different experimental techniques and theoretical calculations. It is confirmed that the chromium tribromide monolayer retains its ferromagnetic order and induces proximitized magnetism on the underlying superconductor niobium diselenide. The results contribute to the broader framework of exploiting proximity effects to realize novel phenomena in 2D heterostructures.